Accounting in Latin America - Frezatti, Fábio; Wanderley, Cláudio De Araujo (Research in accounting in emerging economies ;, 2014)
Latin America consists of a diverse set of countries that nonetheless face common political, economic and social problems; in particular, high inequality and volatile growth which have contributed to high levels of poverty. However, since the 2000s, most countries in Latin America have reduced inflation, brought external debts under control and improved on most of the key economic and social performance indexes. These structural changes have attracted the attention of external investors, as well as large international audiences. With countries such as Mexico and Brazil becoming political and economic power houses, the Latin American region is set to play an important role in the global economy. Yet, international research communities currently lack a systematic understanding of Latin American accounting issues, in spite of a vibrant and growing accounting literature emanating from Latin American researchers. We aim with this volume to offer to the external audiences a sample of the research conducted in Latin American countries ranging from issues of financial and management Accounting, which can further theirs understanding of accounting issues in Latin America.